Determination of the predictive Reliability for PEMFC system - Nedjem Eddine Benchouia; Lakhdar Khochemane; Belgacem Madi (IPCO, 2015)
Today reliability is one of the serious requirements of fuel cell systems, and their associated cost in all applications, in general, and automotive applications, in particular when the power requirement is scaled up, is still unclear. Therefore, increasing cell lifetimes and membrane electrode assembly (MEA) durability is the technical advance that may be expected so that we can have a remarkable tendency of decreasing fuel cell costs with a significant increase in global systems safety, that best meet customer requirements. Our contribution, in this paper, focuses on the simulation method of the “Monte Carlo” over the entire reliability calculation for the PEMFC system, with the integration of the most critical elements of them and the proposition of the contrivances for their modifications, in the objective to predict the lifetime and failure rate of a system by reliability calculations: a problem formulation is given, reliability calculations of PEMFC are defined and a reliability estimation methodology is developed. We did obtain, however, some results that can help us in the prediction reliability way at the design